Composite positive plate, preparation method of composite positive plate, secondary battery and electric equipment

By printing the solid electrolyte pattern with interval settings on the positive electrode of the lithium-ion battery, the safety accident problem that lithium-ion batteries may cause in abnormal situations is solved, and the safety performance and thermal stability of the battery are improved while maintaining the The energy density of the battery and reduce manufacturing costs.

CN119419255AActive Publication Date: 2025-02-11XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411729373.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Existing lithium-ion batteries may cause short circuits within the battery under overcharging, physical damage or other abnormal situations, which will lead to safety accidents such as overheating, explosion or fire. Methods to improve battery material and structural design will affect the energy density and manufacturing of the battery. efficiency.

Method used

A layer of solid electrolyte pattern arranged at intervals is printed on the positive electrode sheet to form a plurality of solid electrolyte patterns arranged at intervals, reducing the impact of the solid electrolyte layer on the battery energy density, while improving the thermal stability of the battery cell and the battery safety performance.

Benefits of technology

By coating the solid electrolyte layer in printed form, the safety performance and thermal stability of the battery are improved, the impact on the battery's energy density is reduced, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419255A_ABST
    Figure CN119419255A_ABST
Patent Text Reader

Abstract

The invention discloses a composite positive plate, a preparation method of the composite positive plate, a secondary battery and electric equipment. Compared with a full coating mode, the printed coating mode has the advantages that the influence of the solid electrolyte layer on the energy density of the lithium ion battery is reduced, and the safety performance of the battery is improved; the area and the spacing of the solid electrolyte pattern are controllable, so that the influence on the charge-discharge performance of the battery is reduced, and the influence on the energy density and the cycle energy of the battery is reduced; and meanwhile, the printing type coating can improve the liquid retention capability of the pole piece and effectively improve the cycle capability of the battery cell, so that the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite positive electrode sheet, a preparation method of the composite positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Ternary lithium-ion batteries have become an indispensable energy storage method in mobile electronic devices, electric vehicles and energy storage systems due to their high energy density, long life and good charging performance. However, with the widespread application of lithium-ion batteries, their safety issues have also received increasing attention. Lithium-ion batteries may cause internal short circuits in batteries when overcharged, physically damaged or in other abnormal conditions, leading to safety accidents such as battery overheating, explosion or fire.

[0003] In order to improve the safety performance of lithium-ion batteries, existing technologies mainly focus on improving battery materials and structural design. For example, by using more stable and safer electrolyte materials, such as solid electrolytes, to replace traditional liquid electrolytes; or by improving the chemical composition of the positive and negative electrode materials of the battery to improve the thermal stability of the battery.

[0004] Although existing technologies have improved the safety performance of lithium-ion batteries to a certain extent, there are still some problems and limitations. First, although the use of solid electrolytes can improve the safety of batteries, it will significantly reduce the energy density of batteries, affecting the performance and capacity of batteries. Secondly, although improving battery materials and structural design can improve the safety of batteries, it requires large-scale transformation of existing battery production processes, which is costly and may affect the manufacturing efficiency of batteries. Therefore, how to further improve the safety performance of lithium-ion batteries without significantly reducing the energy density of batteries is a problem that needs to be solved urgently in this field. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0006] To this end, embodiments of the present invention provide a composite positive electrode sheet, a method for preparing the composite positive electrode sheet, a secondary battery, and an electrical device.

[0007] In a first aspect, the present invention provides a composite positive electrode sheet, comprising:

[0008] Positive electrode;

[0009] A solid electrolyte layer is printed on the entire surface of the positive electrode plate, and the solid electrolyte layer includes a plurality of solid electrolyte patterns arranged at intervals.

[0010] The present invention utilizes the safety of solid electrolytes by printing and coating the solid electrolyte layer on the positive electrode plate at intervals, reduces the impact of the solid electrolyte layer on the battery energy density, increases the liquid retention capacity of the plate, effectively increases the thermal stability of the battery cell, and improves the safety performance of the battery.

[0011] Furthermore, the distance between two points on the solid electrolyte pattern is within 10 μm, and the area of ​​one side of the solid electrolyte pattern corresponding to the positive electrode sheet is 1 to 80 μm. 2 .

[0012] The side of the solid electrolyte pattern corresponding to the positive electrode is the side where the solid electrolyte pattern contacts the positive electrode. The appropriate area improves the safety of the solid-state battery, reduces the impact of the solid electrolyte on the energy density of the battery, enhances the liquid retention capacity of the electrode, and improves the thermal stability of the battery cell; if the area is too large, the internal resistance of the battery will increase, thereby reducing the output power and energy density of the battery; if the area is too small, an effective ion conduction network cannot be formed, resulting in an increase in the internal resistance of the battery and reduced battery performance.

[0013] The area of ​​a single solid electrolyte pattern of the present invention is 1 to 80 μm 2 Moreover, the distance between two points on the solid electrolyte pattern is within 10 μm. The smaller the area of ​​the solid electrolyte pattern and the smaller the spacing, the larger the specific surface area of ​​the overall pattern and the more seepage paths of the electrolyte, which makes the seepage faster and improves its liquid retention capacity.

[0014] Furthermore, the distance between the centers of two adjacent solid electrolyte patterns is 1-10 μm.

[0015] The distance between the centers of two adjacent solid electrolyte patterns can be 1μm, 3μm, 5μm, 8μm, 10μm or a value within a range consisting of any two values. The appropriate distance between two adjacent solid electrolyte patterns reduces the impact of the solid electrolyte layer on the battery's charge and discharge performance, thereby reducing the impact on the battery's energy density and cycle capacity. When the distance between two adjacent solid electrolyte patterns is too large, the solid electrolyte layer cannot effectively cover the positive electrode sheet, thereby affecting the safety performance of the battery; when the distance is too small, the battery's energy density and the electrode's ability to retain liquid are affected.

[0016] Furthermore, the thickness of the solid electrolyte pattern is less than 10 μm.

[0017] The thickness of the solid electrolyte pattern may be 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 10 μm, or a value within a range consisting of any two of these values.

[0018] The appropriate thickness of the solid electrolyte layer can balance the safety and performance of the battery. It can effectively isolate the positive and negative electrodes, reduce the risks of short circuit and thermal runaway, and ensure the conductivity of ions and smooth charge transfer. It can provide sufficient mechanical strength to avoid rupture or damage during battery manufacturing and use. It can reduce interface problems between the positive electrode and the solid electrolyte layer, improve the efficiency of charge transfer, and enhance battery performance. It can maintain the liquid retention capacity of the electrode, prevent electrolyte leakage, and ensure the performance and life of the battery.

[0019] When the thickness of the solid electrolyte is too large, the internal resistance of the battery increases, thereby reducing the output power and energy density of the battery; the conductivity of the ions is reduced, resulting in slower charging and discharging of the battery and longer charging time; the manufacturing cost of the battery is increased; and the weight of the battery is increased, thereby reducing the energy density of the battery.

[0020] If the thickness of the solid electrolyte layer is too small, it cannot effectively isolate the positive and negative electrodes, increasing the risk of short circuit and thermal runaway, and reducing the safety performance of the battery; resulting in a decrease in mechanical strength, which is prone to rupture or damage during battery manufacturing and use; and increasing interface problems between the positive electrode and the solid electrolyte layer, resulting in poor charge transfer and reducing battery performance.

[0021] Furthermore, the solid electrolyte pattern is one or more of a circle, a triangle or a square.

[0022] It can be understood that the shape of the solid electrolyte pattern can be a regular or irregular pattern, and the shape of the solid electrolyte pattern is not limited and can be selected according to specific working conditions.

[0023] In a second aspect, the present invention provides a method for preparing the composite positive electrode sheet provided in the first aspect, such as Figure 1 As shown, the following steps are included:

[0024] Prepare the positive electrode;

[0025] Prepare solid electrolyte slurry: mix solid electrolyte powder and binder, add solvent and stir evenly;

[0026] The solid electrolyte slurry is coated on the positive electrode plate by a printing process, and dried to obtain a composite positive electrode plate.

[0027] The positive electrode sheet may be a lithium nickel cobalt manganese oxide positive electrode sheet, a lithium iron phosphate positive electrode sheet, or other suitable positive electrode sheets.

[0028] Furthermore, the drying temperature is 100-200° C., and the drying time is 1-10 hours. After the solid electrolyte slurry is coated on the positive electrode sheet, it is placed in an oven for drying to obtain a solidified solid electrolyte layer.

[0029] Furthermore, the solid electrolyte includes an oxide solid electrolyte.

[0030] Oxide solid electrolytes have high ionic conductivity and good stability, which can improve the safety performance of the battery while minimizing the impact on the battery energy density. Among them, the oxide solid electrolyte can be LATP, LLZO, LLTO, LLZTO, etc. It can be understood that the solid electrolyte can also be a sulfide solid electrolyte or a polymer solid electrolyte.

[0031] Furthermore, the binder includes one or more of PVDF, PEO, PVA, PAA, and PMMA.

[0032] Furthermore, the solvent includes one or more of NMP, acetonitrile, acetone, and ethanol, and the mixture of the solid electrolyte and the binder is coated on the positive electrode plate using the solvent as a carrier.

[0033] Furthermore, the added amount of the binder is 5% to 20% of the mass of the solid electrolyte powder.

[0034] The appropriate amount of binder added can ensure good adhesion between the oxide solid electrolyte slurry and the electrode surface, preventing the coating from falling off during the battery charging and discharging process; it can form a uniform coating, which is beneficial to the conduction of ions, thereby improving the performance of the battery; the oxide solid electrolyte itself has high thermal stability, and the appropriate amount of binder added can further enhance the thermal stability of the coating and reduce the risk of thermal runaway.

[0035] When too little binder is added, the adhesion between the oxide solid electrolyte slurry and the electrode surface is insufficient, the coating is easy to fall off, and the safety and performance of the battery cannot be formed. The coating is unable to form a uniform coating, resulting in decreased thermal stability and increased risk of thermal runaway. The coating lacks sufficient mechanical strength and is prone to cracks during the battery charging and discharging process, affecting the long-term stability and safety of the coating.

[0036] When too much binder is added, the coating becomes thicker, increasing the internal resistance of the battery, thereby reducing the battery performance; hindering the conduction of ions, resulting in a decrease in the battery's charge and discharge efficiency; increasing the battery's production cost; making the coating more brittle and prone to cracking during the battery's charge and discharge process, affecting the long-term stability and safety of the coating.

[0037] Furthermore, the particle size of the solid electrolyte powder is 0.2-0.8 μm.

[0038] The appropriate solid electrolyte powder particle size can provide more ion transmission channels, thereby improving the ion conductivity of the coating, helping to reduce the impedance inside the battery and improve the battery's charge and discharge efficiency; it can form a denser coating, thereby enhancing the mechanical strength of the coating, helping to resist the physical stress that the battery may encounter during use, such as bending, impact, etc.; it can better contact with the electrode material to form a stable interface, helping to reduce side reactions at the interface and improve the battery's cycle stability.

[0039] When the particle size of the solid electrolyte powder is too large, more grain boundaries and defects will be formed inside the coating, thereby reducing the ion conductivity of the coating, increasing the impedance inside the battery, and reducing the battery's charge and discharge efficiency; the coating formed by particles that are too large may not be dense enough and have low mechanical strength, causing the coating to easily break under physical stress, thereby affecting the safety and life of the battery; it will lead to poor contact with the electrode material, increase the interfacial impedance, increase the impedance inside the battery, and reduce the battery's charge and discharge efficiency and cycle stability.

[0040] If the particle size of the solid electrolyte powder is too small, the coating formed may not be dense enough and have low mechanical strength, causing the coating to easily break under physical stress, thus affecting the safety and life of the battery; it forms poor contact with the electrode material, resulting in increased interface impedance, which in turn increases the impedance inside the battery and reduces the battery's charge and discharge efficiency and cycle stability; more preparation steps and equipment are required, thereby increasing production costs; in addition, particles that are too small are also more likely to agglomerate during storage and transportation, thus affecting their performance.

[0041] In a third aspect, the present invention provides a secondary battery comprising the composite positive electrode sheet provided in the first aspect or the composite positive electrode sheet prepared by the method provided in the second aspect.

[0042] In a fourth aspect, the present invention provides an electrical device comprising the secondary battery provided in the third aspect.

[0043] Compared with the prior art, the beneficial effects of the present invention are:

[0044] The present invention coats a solid electrolyte layer on the positive electrode sheet, which effectively increases the thermal stability of the battery cell and improves the safety performance of the battery while exerting the safety of the solid electrolyte.

[0045] The present invention adopts a printed coating method, which reduces the impact of the solid electrolyte layer on the energy density of the lithium-ion battery and improves the safety performance of the battery compared to the full coating method; the area and spacing of the solid electrolyte pattern are controllable, which reduces the impact on the battery's charge and discharge performance, thereby reducing the impact on the battery's energy density and cycle energy; at the same time, the printed coating can increase the electrode's liquid retention capacity, effectively improve the battery cell's cycle capacity, and thus increase the battery's service life.

[0046] The present invention adopts printing coating to reduce the amount of solid electrolyte coated and maintain the portability of the battery; at the same time, the printing coating method is easier to implement than the full coating method, and the required materials and processes are simpler, thereby reducing the manufacturing cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0048] Figure 1 The present invention is a flow chart of the method for preparing the composite positive electrode sheet. DETAILED DESCRIPTION

[0049] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0050] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0051] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0052] Example 1

[0053] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0054] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was in the shape of dots, the diameter of the dot pattern was 2 μm, the spacing between the dot patterns was 5 μm, and the thickness was 10 μm.

[0055] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0056] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0057] Example 2

[0058] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0059] A lithium nickel cobalt manganese oxide positive electrode sheet is prepared, and a solid electrolyte slurry is printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern is in the shape of dots, the diameter of the dot pattern is 2 μm, the spacing between the dot patterns is 5 μm, and the thickness is 4 μm.

[0060] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0061] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0062] Example 3

[0063] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0064] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was in the shape of dots, the diameter of the dot pattern was 5 μm, the spacing between the dot patterns was 5 μm, and the thickness was 10 μm.

[0065] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0066] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0067] Example 4

[0068] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0069] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was in the shape of dots, the diameter of the dot pattern was 5 μm, the spacing between the dot patterns was 8 μm, and the thickness was 10 μm.

[0070] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0071] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0072] Example 5

[0073] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0074] A lithium nickel cobalt manganese oxide positive electrode sheet is prepared, and a solid electrolyte slurry is printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern is in the shape of dots, the diameter of the dot pattern is 10 μm, the spacing between the dot patterns is 10 μm, and the thickness is 10 μm.

[0075] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0076] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0077] Example 6

[0078] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0079] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was square, the side length of the square pattern was 3 μm, the spacing between the dot patterns was 7 μm, and the thickness was 6 μm.

[0080] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0081] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0082] Example 7

[0083] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0084] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was an equilateral triangle shape, the side length of the equilateral triangle pattern was 8 μm, the spacing between the dot patterns was 9 μm, and the thickness was 5 μm.

[0085] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0086] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0087] Comparative Example 1

[0088] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0089] A lithium nickel cobalt manganese oxide positive electrode sheet is prepared, and a solid electrolyte slurry is printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern is in the shape of dots, the diameter of the dot pattern is 2 μm, the spacing between the dot patterns is 15 μm, and the thickness is 4 μm.

[0090] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0091] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0092] Comparative Example 2

[0093] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0094] A lithium nickel cobalt manganese oxide positive electrode sheet was prepared, and a solid electrolyte slurry was printed and coated on the positive electrode sheet, wherein the solid electrolyte pattern was in the shape of dots, the diameter of the dot pattern was 2 μm, the spacing between the dot patterns was 5 μm, and the thickness was 15 μm.

[0095] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0096] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0097] Comparative Example 3

[0098] 100 g of solid electrolyte powder was mixed with 5 ml of binder PVDF, 200 ml of NMP was added, and the mixture was stirred evenly to obtain a solid electrolyte slurry.

[0099] Prepare a lithium nickel cobalt manganese oxide positive electrode sheet, and evenly coat the solid electrolyte slurry on the surface of the positive electrode sheet. The thickness of the solid electrolyte is 10 μm.

[0100] The positive electrode sheet coated with the solid electrolyte layer was placed in an oven and cured for 5 hours at a temperature of 120° C. to obtain a cured solid electrolyte layer.

[0101] The positive electrode plates coated with the solid electrolyte layer are assembled into a lithium battery, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0102] Comparative Example 4

[0103] Prepare lithium nickel cobalt manganese oxide positive electrode sheets, assemble the positive electrode sheets into lithium batteries, and the specific operation steps are carried out according to the conventional lithium battery manufacturing process.

[0104] The lithium battery manufacturing process includes the following steps:

[0105] Positive electrode sheet: The positive electrode slurry includes NCM, SP and PVDF in a mass ratio of 96:2:2. The positive electrode slurry is coated on the current collector. The surface density of the positive electrode slurry coating is 19.8 mg / cm 2 ; After roller pressing, the compaction density is 3.5g / cm 3 , after die-cutting, a pole piece with a length and width of 90×59mm is obtained; NCM refers to nickel-cobalt-manganese ternary positive electrode material, SP refers to conductive carbon black, and PVDF refers to polyvinylidene fluoride;

[0106] Negative electrode sheet: The negative electrode slurry includes graphite, conductive agent (SP), binder (SBR) and thickener (CMC) in a mass ratio of 95.5:1:2:1.5; the negative electrode slurry is coated on the current collector with a coating surface density of 11.5 mg / cm 2 , after rolling and die cutting, a negative electrode sheet with a length and width of 93×62 mm was obtained;

[0107] Diaphragm: The diaphragm is PP / PE diaphragm;

[0108] The positive electrode / diaphragm / negative electrode method is used for stacking, and after stacking, a soft package is used for packaging, liquid injection, and sealing to obtain a 5Ah battery.

[0109] The test method of battery puncture test: use a 5mm diameter steel needle to pierce the battery at a speed of 25mm / s, stay inside the battery for 60 minutes, and observe whether there is fire, explosion, etc. If there is no fire or explosion, the test passes.

[0110] The test method of battery overcharge test: the initial voltage of the battery is 4.2V, and it is charged with a constant current of 1C to 6.3V or stop charging after the charging time reaches 1h, and observe whether there is fire, explosion and other phenomena. If there is no fire or explosion, the test has passed.

[0111] Battery energy density test method:

[0112] ①Discharge at 1 / 3C constant current until the end voltage is reached, and then stand for 30 minutes;

[0113] ② Charge at 1 / 3C constant current until the termination voltage is reached, then switch to constant voltage charging until the charging current drops to 0.05C, then stop charging and let stand for 30 minutes;

[0114] ③Discharge at 1 / 3C constant current until the end voltage is reached, then stand for 30 minutes and record the discharge capacity and average discharge voltage;

[0115] ④ Calculate battery energy density = battery capacity * average discharge voltage / battery weight.

[0116] Battery cycle performance test method:

[0117] ①Discharge at 1C constant current until the end voltage is reached, then stop discharging and let stand for 30 minutes;

[0118] ② Charge at 1C constant current until the termination voltage is reached, then switch to constant voltage charging until the charging current drops to 0.05C, then stop charging and let stand for 30 minutes;

[0119] ③Discharge at 1C constant current until the end voltage is reached, then stand for 30 minutes and record the discharge capacity;

[0120] ④ Cycle ② to ③ continuously for 500 times, and take the ratio of the 500th discharge capacity to the initial discharge capacity as the discharge capacity retention rate.

[0121] The lithium ion batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were subjected to energy density, cycle performance, puncture and overcharge tests, wherein three batteries were tested in each test, and the energy density and discharge capacity retention rate were the average values ​​of the three batteries. The test results are shown in Table 1.

[0122] Table 1:

[0123]

[0124]

[0125] By comparing Examples 1 to 7 with Comparative Examples 3 and 4, it can be seen that after coating the solid electrolyte layer on the positive electrode plate, the safety performance of the battery is improved; compared with full-coverage coating, the energy density and cycle performance of the printed coated battery are significantly improved. At the same time, the puncture and overcharge test results show that the safety performance of the printed coated battery is consistent with that of the full-coverage coating.

[0126] By comparing Example 2 with Comparative Example 1, it can be seen that when the spacing between the dot patterns of the coating layer is too large, the energy density and cycle performance of the battery are improved, but the safety performance is reduced.

[0127] By comparing Example 2 and Comparative Example 2, it can be seen that when the thickness of the dot pattern of the coating layer is too large, the energy density and cycle performance of the battery are reduced, and the safety performance is consistent.

[0128] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0129] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0130] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A composite positive electrode sheet, characterized in that: include: Positive electrode; A solid electrolyte layer is printed on the entire surface of the positive electrode plate, and the solid electrolyte layer includes a plurality of solid electrolyte patterns arranged at intervals.

2. The composite positive electrode sheet according to claim 1, characterized in that: The distance between two points on the solid electrolyte pattern is within 10 μm, and the area of ​​one side of the solid electrolyte pattern corresponding to the positive electrode sheet is 1 to 80 μm. 2 .

3. The composite positive electrode sheet according to claim 2, characterized in that: The distance between the centers of two adjacent solid electrolyte patterns is 1 to 10 μm; And / or, the thickness of the solid electrolyte pattern is less than 10 μm.

4. The composite positive electrode sheet according to claim 1, characterized in that: The solid electrolyte pattern is one or more of a circle, a triangle or a square.

5. A method for preparing a composite positive electrode sheet, characterized in that: The method for preparing the composite positive electrode sheet according to any one of claims 1 to 4 comprises the following steps: Prepare the positive electrode; Prepare solid electrolyte slurry: mix solid electrolyte powder and binder, add solvent and stir evenly; The solid electrolyte slurry is coated on the positive electrode plate by a printing process, and dried to obtain a composite positive electrode plate.

6. The method according to claim 5, characterized in that The solid electrolyte comprises an oxide solid electrolyte; And / or, the binder includes one or more of PVDF, PEO, PVA, PAA, and PMMA; And / or, the solvent includes one or more of NMP, acetonitrile, acetone, and ethanol.

7. The method according to claim 5, characterized in that The added amount of the binder is 5% to 20% of the mass of the solid electrolyte powder.

8. The method according to claim 5, characterized in that The particle size of the solid electrolyte powder is 0.2-0.8 μm.

9. A secondary battery, characterized in that: The invention comprises the composite positive electrode sheet as claimed in any one of claims 1 to 4 or the composite positive electrode sheet prepared by the method as claimed in any one of claims 5 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.

Citation Information

Patent Citations

  • Composite positive pole piece, preparation method thereof and lithium battery

    CN116053401A

  • Method for manufacturing support for lithographic printing plate, support for lithographic printing plate, and lithographic printing original plate

    JP2003019877A

  • Secondary Battery

    US20240113332A1